Significance of journal paper publication and guideline in postgraduate study - Masjuki, Haji Hassan; Sattar, M.A.; Mahlia, Teuku Meurah Indra; Kalam, Md. Abul; Husnawan, M.; Saidur, Rahman (2009)

(untitled)
In a recent change of policy reviewed by University of Malaya (UM) postgraduate students are required to publish journal paper before they are awarded their degrees. In a new curriculum effective from 18 December 2008, postgraduate students by research mode are required to publish minimum of one Institutes of Scientific Information (ISI) journal paper for Master degree and two ISI journal papers for Doctor of Philosophy (Ph.D.) degree. Public universities are fervent for paper publication as it has an impact on university world ranking so the requirement is designed to boost the number of journal paper publication of the university and a good opportunity of the student’s future career. The paper publication increases critical thinking, data analysis skill of the student and many other obvious advantages. University of Malaya has global recognition with state of the art research facility and provides student with fellowship and research assistantship for financial aid so that student can accomplish the desired goal. Students can apply for short term Research and Development (R&D) grant named as postgraduate research fund for the expenditure of their research purposes. This paper discusses the significance of publishing journal paper by postgraduate student to fulfill University requirement and their future career development. The mutual benefit between student and university for publishing journal was also highlighted.